The Art of Maulid Ad-Diba' Between Tradition and Islam in the Archipelago from a Multicultural Education Perspective - Miftahul Huda (Mimbar Agama dan Budaya, 2024)
Multicultural education developed during this period is not prioritized based on community traditions. This research aims to explain that the Islamic tradition of Mawlid Ad-Diba' art or Islamic teachings, Islamic traditions in the archipelago can be used as a basis for multicultural education and the values of multicultural education contained in the art of Mawlid ad-Diba'. This research method is library research with a phenomenological approach and using documentation techniques. The research results show 1) an Islamic tradition; 2) Islam in the archipelago is a form of Islamic moderation, 3) multicultural education based on Islamic traditions, 4) the values of multicultural education: spiritual, social, moral, and unity. The research concludes that the art of Maulid ad-Diba' is not an Islamic teaching in the archipelago but is an Islamic tradition and can be used as a basis for multicultural education that has the values of faith and piety, gratitude, humility, honesty, friendliness, fair, patient.